EXPLORING STUDENTS’ REFLECTIVE JOURNALS IN MICRO TEACHING CLASS BASED ON THE “DIEP” MODEL - Salsabila, Putri; Noni, Nurdin; Korompot, Chairil Anwar (JTechLP: Journal of Technology in Language Pedagogy, 2024)
The main purpose of this research was to explore students' reflective journals using the DIEP model in micro-teaching classes. The author tried to investigate whether writing learning outcomes using the DIEP model reflection journal could provide a new way of understanding students' learning outcomes. In this research, the author conducted semi-structured interviews. The subjects of this study were 10 5th semester students in the micro teaching class. The stages in obtaining data began with writing learning outcomes in the reflective journal using the DIEP model, then an interview session was conducted to obtain more accurate data. The results of this study indicate that writing learning outcomes using the DIEP model reflective journal can have a positive impact on the memory of learning outcomes, as well as developing thinking skills. This can be proven from the results of interviews conducted directly, students felt a significant difference between writing learning outcomes in the DIEP model reflection journal and the way they remembered previous learning outcomes. This means that the use of the DIEP model reflection journal can be one of the media used to store a longer memory of learning outcomes.